Biologic treatments for elderly patients with psoriasis. Issue 9 (25th April 2017) - Momose, Mami; Asahina, Akihiko; Hayashi, Mitsuha; Yanaba, Koichi; Umezawa, Yoshinori; Nakagawa, Hidemi
Abstract: The number of elderly patients with psoriasis is increasing in Japan. However, biologic treatment is generally considered to be challenging in elderly patients, due to their increased risk of complications compared with younger patients. Our retrospective study aimed to evaluate the safety profile and efficacy of biologics in senior elderly patients (≥75 years old) with psoriasis. The study involved a cohort of 27 patients aged 75–88 years who were being treated with biologics over a period of more than 1 year. Initial biologics administrated to were adalimumab (five cases) and ustekinumab (22 cases). Eight patients discontinued treatment: two developed cancer; one was transferred to hospital; and five others experienced either bone fracture, interstitial pneumonia, cerebral hemorrhage resulting in death, decrepitude or developed hepatopathy following prophylactic tuberculosis treatment. Efficacy, evaluated by the percentage of patients achieving 75% reduction of Psoriasis Area and Severity Index score, was 76.9% at week 16 ( n = 26), 88.0% at week 24 ( n = 25) and 90.5% at week 52 ( n = 21). Biologic treatments thus show clear efficacy in elderly patients with psoriasis, however, the increased frequency of adverse events requires rigorous patient observation.